2016
DOI: 10.1002/ejoc.201501560
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Approach to the Total Synthesis of Ammosamide B

Abstract: Abstract:A new approach for the total synthesis of ammosamide B was realized. The strategy is based on an intermolecular Pd-catalyzed N-arylation of 4-chloro-1-methylindoline-2,3-dione (2), which enables construction of the key pyrroloquinoline skeleton precursor 6 within three steps in an overall yield of 80 %. The ammosamide B total synthesis is achieved in 12

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…These compounds were originally found to possess activity against HCT-116 cells by targeting the cellular cytokinetic protein myosin, each with IC 50 = 320 nM. 57 , 58 Throughout the next few years 25 would be synthesized several times by notable groups 59 , 60 , 61 , 62 , however, in 2012 Reddy et al . synthesized several analogs and tested for their quinone reductase 2 (QR2) activity.…”
Section: Natural Products Which Have Benefited From Analog Developmenmentioning
confidence: 99%
“…These compounds were originally found to possess activity against HCT-116 cells by targeting the cellular cytokinetic protein myosin, each with IC 50 = 320 nM. 57 , 58 Throughout the next few years 25 would be synthesized several times by notable groups 59 , 60 , 61 , 62 , however, in 2012 Reddy et al . synthesized several analogs and tested for their quinone reductase 2 (QR2) activity.…”
Section: Natural Products Which Have Benefited From Analog Developmenmentioning
confidence: 99%
“…In Scheme , benzo­[ cd ]­indol-2­(1 H )-one derivatives were prepared (Tables and ). The synthesis of intermediate 39 is no longer described in the same way as reported by Yang et al Starting from inexpensively available 4-chloroindoline-2,3-dione, the intermediate was nitrated with nitric acid sulfuric acid system from −25 to −10 °C to afford compound 40 . Intermediates 43 and 44 were synthesized from 39 by hydrogenation and dechlorination.…”
Section: Chemistrymentioning
confidence: 99%
“…make their further derivatization become meaningful and attractive. In our preliminary work on the total synthesis of ammosamide B, 2 we found that the compound has poor hydrophilic and lipophilic solubility when the amino groups were exposed. Fortunately, the lipophilic solubility was improved when the amino groups were acylated.…”
mentioning
confidence: 99%